2021
DOI: 10.1002/jper.21-0212
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two types of xenogeneic matrices to treat single gingival recessions: A randomized clinical trial

Abstract: Background: Xenogeneic matrices (XMs) have been increasingly used for root coverage procedures. This study compared the use of two types of XM (collagen matrix [CM] and xenogeneic acellular dermal matrix [XDM]) associated with the coronally advanced flap technique (CAF) to treat single gingival recessions.Methods: Seventy-five patients presenting single RT1 gingival recession were treated by CAF (control group, n = 25), CAF+CM (test group 1, n = 25), or CAF+XDM (test group 2, n = 25) and completed 6-month foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 44 publications
2
19
0
Order By: Relevance
“…Data for mean RecRed and KTW gain were available for all studies. Seven studies reported TKT gain (Fernandes-Dias et al, 2015;Santamaria et al, 2016Santamaria et al, , 2017Santamaria et al, , 2018Santamaria et al, , 2021Cairo et al, 2020;Mathias-Santamaria et al, 2021). Ten studies assessed the percentage of mean RC (McGuire & Nunn, 2003;Cortellini et al, 2009;Cairo et al, 2012;Fernandes-Dias et al, 2015;Santamaria et al, 2017Santamaria et al, , 2018Santamaria et al, , 2021Clementini et al, 2018;Nahas et al, 2019;Mathias-Santamaria et al, 2021).…”
Section: Synthesis Of the Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Data for mean RecRed and KTW gain were available for all studies. Seven studies reported TKT gain (Fernandes-Dias et al, 2015;Santamaria et al, 2016Santamaria et al, , 2017Santamaria et al, , 2018Santamaria et al, , 2021Cairo et al, 2020;Mathias-Santamaria et al, 2021). Ten studies assessed the percentage of mean RC (McGuire & Nunn, 2003;Cortellini et al, 2009;Cairo et al, 2012;Fernandes-Dias et al, 2015;Santamaria et al, 2017Santamaria et al, , 2018Santamaria et al, , 2021Clementini et al, 2018;Nahas et al, 2019;Mathias-Santamaria et al, 2021).…”
Section: Synthesis Of the Resultsmentioning
confidence: 99%
“…Table 2 depicts the general characteristics of the included studies. Two RCTs were conducted with split‐mouth design (McGuire & Nunn, 2003; Nahas et al, 2019) and 11 were conducted with a parallel group (Cortellini et al, 2009; Cairo et al, 2012, 2020; Fernandes‐Dias et al, 2015; Santamaria et al, 2016, 2017, 2018, 2021; Clementini et al, 2018; Tonetti et al, 2018; Mathias‐Santamaria et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations